Sea Wave Energy Estimating in front of the Iraqi Coast, Northwest Arabian Gulf - Adel Jassim Al-Fartusi; Sajjad k. Chasib ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The world is turning to alternative energies (wind energy, solar energy, and seawater energy) as eco-friendly and renewable energy. The monthly and seasonal averages of the sea wave energy (i.e., total and characteristic wave energy) were studied in the northwest Arabian Gulf in front of the Iraqi coast in the OUTER BAR. A mathematical analysis was conducted for 3560 wind speed values (2015-2024). The results showed that the total energy of the sea wave was limited between the two values 55.42 and 581.19 (Joules/m2), while the characteristic wave energy was restricted between 102.09 and 2855.87 (Joules/m2). Also, the seasonal wave energy is within the range of 73.84 - 423.53 (Joules/m2), and the seasonal wave energy median is within the range of 116.87-1579.21 (Joules/m2). The standard deviation value σ was also determined, which reflects the extent of energy dispersion around the seasonal peak. The results may provide future insights into how sea structures and barriers are built when these calculations are used appropriately.DOI: https://doi.org/10.54633/2333-025-058-006